A gestão da marca do profissional liberal: um estudo de caso na área médica na cidade de São Paulo - Nishioka, Ligia Cristina (2013)
As attitudes and experiences facilitate the purchasing decision process and consumer, brands also assume a very important role for the consumer to decide between the many options available, both for goods and for services. It happens that, in recent years, it has been noticed that brands concept go beyond products and services. Individuals and organizations can also be viewed as a brand. Anyone who is trying to build his career may consider creating your own brand. As manufacturing companies or service providers, the independent professionals also seek to excel in the market and differentiate themselves from other competitors. Therefore, the professional, in order to manage and consolidate his name in the field of work could get efficient results using the same tools used by companies. Accordingly, this paper aims to determine whether physicians, as an independent professionals example, adopt the brand identity tools to his name in order to design professionally. We opted for a qualitative approach with one single case study for physicians profession, in order to understand how these professionals think and act on the matter. From the results, it is concluded that medical professionals do not adopt the brand identity tools to his name to design professionally, and signaled a high degree of resistance to such use